Company Reputation, Product Quality and Price Affect Customer Loyalty One-Door Refrigerator Products in Takengon City - Eliyin, Eliyin; Rayuwati, Rayuwati; Yustisar, Muhamad; Gemasih, Husna (Publisher Cv. Inara, 2022)
This study analyzes the Company's Reputation, Product Quality and Price on Customer Loyalty of one-door refrigerators product in Takengon City. The research uses a quantitative research approach with associative methods. The population in the study amounted to 251 customers of the Sinar Matahari store in Takengon City, with a total sample of 68 respondents. The sampling technique used was non-probability sampling, with the accidental sampling method. The data analysis technique used multiple linear regression analysis. The research data is sourced from primary data and the data collection process uses interviews, questionnaires and observations. Based on the results of multiple linear regression analysis, it is known that the results of the t test for the Company's Reputation variable are 1.222 and significant 0.226 > 0.05, which means that the Company's Reputation partially has no positive and significant effect on Customer Loyalty, Product Quality variable is -0.642 and significant 0.000 > 0 0.05, which means that the location partially has no positive and significant effect on customer loyalty and the price variable is 4.137 and significant 0.000 <0.05, which means that the price partially has a positive and significant effect on customer loyalty. The results of the F test are 20.860 and a significant 0.000 <0.05, which means that the company's reputation, product quality and price simultaneously have a positive and significant effect on customer loyalty. The results of the R2 test show that the Adjusted R Square value of 0.471 means that 47.1% of consumer satisfaction can be obtained and is explained by the variables of Company Reputation, Product Quality and Price.